Allan C. Ornstein i Francis P. Hunkins, Program szkolny: założenia, zasady, problematyka, WSiP, Warszawa 1998, ss. 438. - Piotrowski, Eugeniusz (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
Recenzje i sprawozdania z książek